Legal Analysis of The Implementation of Village Community Participation In Forming Public Policies (Village Regulations) - Saiful Aziz; Muh Saleh; Surawijaya (Journal of Law, Politic and Humanities, 2026)
Study This aim analyze implementation participation public in formation Regulation Village reviewed from perspective juridical . Research use method law juridical empirical with approach qualitative through studies bibliography , interviews , and documentation . Research results show that participation public has implemented through deliberation village in accordance provision regulation legislation , however Still nature procedural and not yet fully reflect meaningful participation . Barriers​ main covering low access information , domination of village elites , and Not yet optimally the role of the Consultative Body Village . Therefore that , is necessary strengthening transparency , empowerment society , and optimization BPD function to realize formation Regulation A democratic , participatory and just village